Targeting and pharmacology of an anti-IL13Rα2 antibody and antibody-drug conjugate in a melanoma xenograft model. Issue 1 (1st January 2021) - Gupta, Parul; Jiang, Ziyue Karen; Yang, Bing; Manzuk, Lisa; Rosfjord, Edward; Yao, Johnny; Lemon, Luanna; Noorbehesht, Kavon; David, John; Puthenveetil, Sujiet; Casavant, Jeffrey M.; Muszynska, Elwira; et al.
ABSTRACT: IL13Rα2 is a cell surface tumor antigen that is overexpressed in multiple tumor types. Here, we studied biodistribution and targeting potential of an anti-IL13Rα2 antibody (Ab) and anti-tumor activity of anti-IL13Rα2-antibody-drug conjugate (ADC). The anti-IL13Rα2 Ab was labeled with fluorophore AF680 or radioisotope 89 Zr for in vivo tracking using fluorescence molecular tomography (FMT) or positron emission tomography (PET) imaging, respectively. Both imaging modalities showed that the tumor was the major uptake site for anti-IL13Rα2-Ab, with peak uptake of 5–8% ID and 10% ID/g as quantified from FMT and PET, respectively. Pharmacological in vivo competition with excess of unlabeled anti-IL13Rα2-Ab significantly reduced the tumor uptake, indicative of antigen-specific tumor accumulation. Further, FMT imaging demonstrated similar biodistribution and pharmacokinetic profiles of an auristatin-conjugated anti-IL13Rα2-ADC as compared to the parental Ab. Finally, the anti-IL13Rα2-ADC exhibited a dose-dependent anti-tumor effect on A375 xenografts, with 90% complete responders at a dose of 3 mg/kg. Taken together, both FMT and PET showed a favorable biodistribution profile for anti-IL13Rα2-Ab/ADC, along with antigen-specific tumor targeting and excellent therapeutic efficacy in the A375 xenograft model. This work shows the great potential of this anti-IL13Rα2-ADC as a targeted anti-cancer agent.